Pengaruh Kesehatan Dan Keselamatan Kerja, Pelatihan Dan Kerja Tim Terhadap Kinerja Karyawan UD Bela Jaya Ps - Asyah Rohmatul; Nurhajati Nurhajati; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The purpose of this study was to determine the effect of work safety, training, and teamwork on the performance of Bela Jaya PS employees. This survey method uses a survey survey method, a survey quantitative approach that takes samples from the population and uses a survey as a primary data collection tool. The sample consisted of 37 individuals who were selected using a targeted sampling technique. As a result, occupational health and safety has a positive effect, and training has a positive effect. Team work has a positive effect. Therefore, occupational health and safety, training and teamwork can also have a positive and significant effect on employee performance. Keywords: health and safety, training and teamwork